Genome-wide identification and expression profiling analysis of maize AP2/ERF superfamily genes reveal essential roles in abiotic stress tolerance - Jing Zhang; Jiayao Liao; Qiqi Ling; Yan Xi; Yexiong Qian (BMC Genomics, 2022)
Abstract Background As one of the largest transcription factor families in plants, the APETALA2/Ethylene-Responsive Factor (AP2/ERF) superfamily is involved in various biological processes and plays significant roles in plant growth, development and responses to various stresses. Although identification and characterization of AP2/ERF superfamily genes have been accomplished in many plant species, very little is known regarding the structure and function of AP2/ERF genes in maize. Results In this study, a total of 214 genes encoding ZmAP2/ERF proteins with complete AP2/ERF domain were eventually identified according to the AGPv4 version of the maize B73 genome. Based on the number of AP2/ERF domain and similarities of amino acid sequences among AP2/ERF proteins from Arabidopsis, rice and maize, all 214 putative ZmAP2/ERF proteins were categorized into three distinct families, including the AP2 family (44), the ERF family (166) and the RAV family (4), respectively. Among them, the ERF family was further subdivided into two diverse subfamilies, including the DREB and ERF subfamilies with 61 and 105 members, respectively. Further, based on phylogenetic analysis, the members of DREB and ERF subfamilies were subdivided into four (Group I-IV) and eight (Group V-XII) groups, respectively. The characteristics of exon-intron structure of these putative ZmAP2/ERF genes and conserved protein motifs of their encoded ZmAP2/ERF proteins were also presented respectively, which was in accordance with the results of group classification. Promoter analysis suggested that ZmAP2/ERF genes shared many stress- and hormone-related cis-regulatory elements. Gene duplication and synteny analysis revealed that tandem or segmental duplication and purifying selection might play significant roles in evolution and functional differentiation of AP2/ERF superfamily genes among three various gramineous species (maize, rice and sorghum). Using RNA-seq data, transcriptome analysis indicated that the majority of ZmAP2/ERF genes displayed differential expression patterns at different developmental stages of maize. In addition, the following analyses of co-expression network among ZmAP2/ERF genes and protein protein interaction between ZmAP2 and ZmERF proteins further enabled us to understand the regulatory relationship among members of the AP2/ERF superfamily in maize. Furthermore, by quantitative real-time PCR analysis, twenty-seven selected ZmAP2/ERF genes were further confirmed to respond to three different abiotic stresses, suggesting their potential roles in various abiotic stress responses. Collectively, these results revealed that these ZmAP2/ERF genes play essential roles in abiotic stress tolerance. Conclusions Taken together, the present study will serve to present an important theoretical basis for further exploring the function and regulatory mechanism of ZmAP2/ERF genes in the growth, development, and adaptation to abiotic stresses in maize.